KOMPARASI JAKARTA ISLAMIC INDEX DAN FTSE BURSA MALAYSIA HIJRAH SHARIAH INDEX - Nur Fu’ad Shofiyullah (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2014)
The purpose of this study is to analyze the differences in the performance of the JII Index in Indonesia and FBMHS in Malaysia using the Sharpe, Treynor and Jensen Alpha ratios.The type of this research is hypothesis testing by using purposive sampling techniques. The population in this study is all listed Islamic Indexes in Indonesia Stock Exchange and Bursa Malaysia. Two Indices are obtained from the sampling process, namely Jakarta Islamic Index (JII) and the FTSE Bursa Malaysia Hijrah Shariah Index (FBMHS). Object of this study is the monthly index return for the period of January 2009 to December 2011, amounting to 36 points of data.Hypothesis testing is intended to determine whether there are significant differences between the performance of JII and FBMHS on Sharpe, Treynor and Jensen aspects. The tests carried out using Two Independent Samples Mean Comparison. The results showed that there was no significant difference between the performance of JII and FBMHS on the Sharpe, Treynor and Jensen Alpha ratios.